Eccentricity-induced galloping mechanism of a vertical-torsional coupled 3-DOF system. Issue 229 (October 2022) - Wen, Zuopeng; Xu, Haiwei; Lou, Wenjuan
Abstract: The mass eccentricity in a vertical-torsional coupled system has been recognized as an important reason responsible for galloping initiation. It may be coupled with aerodynamic stiffness to exert complicated effects (e.g. promote or suppress) on galloping instability. However, rare of previous study can illustrate the mechanism explicitly. This paper studied a three-degree-of-freedom (3-DOF) model with close vertical and torsional frequencies. Non-defective and defective perturbation methods were adopted to establish a complete galloping stability criterion considering inertial coupling, significant and insignificant aerodynamic stiffness, and small frequency detuning simultaneously. To explicitly show the influence of mass eccentricity on galloping initiation, an eccentricity criterion consisting of lift force coefficient and eccentric angle was proposed. Wind tunnel test results were employed to examine the validity of the 3-DOF model. The results show that considering both inertial coupling and aerodynamic stiffness together is necessary to provision of reasonable predictions matching galloping test results. The validity of the proposed galloping stability criterion was verified numerically under various wind conditions. The proposed eccentricity criterion was verified reasonable via a conductor with three typical ice accretion shapes. The study finding may increase the understanding of eccentricity-induced galloping mechanism and provide guidance for anti-galloping design. Highlights: Eccentricity-induced galloping mechanism is revealed for a coupled 3-DOF system. A galloping stability criterion is proposed for a vertical-torsional coupled system. Effects of aerodynamic stiffness and inertial coupling on galloping are explained. An eccentricity criterion is presented to show how eccentricity affects galloping.